Diffusional homogenization of light REE in garnet from the Day Nui Con Voi Massif in N-Vietnam: Implications for Sm–Nd geochronology and timing of metamorphism in the Red River shear zone. - Anczkiewicz, R; Thirlwall, Matthew; Alard, Oliver; Rogers, N; Clark, Chris (Elsevier Science BV, 2012)
High-grade migmatitic and mylonitic gneisses from the Day Nui Con Voi massif in northern Vietnam record temperatures of 760–810 °C at pressures of 6–10 kbars. High temperature conditions have resulted in the development of major element diffusional profiles in garnet. Laser ablation ICP-MS analyses of trace elements indicate that REE and Hf closely followed Rayleigh-like fractionation trends but underwent significant post-crystallization modification. Light REE and to a lesser extent, HREE rim-to-rim zonation profiles show progressive flattening with the decreasing garnet size. Nd and Sm are completely homogenized in the crystals smaller than 1.5 mm, while Lu always preserves variable degrees of core-to-rim concentration gradient. The observed REE patterns are interpreted as resulting from the combination of protracted garnet growth of progressively smaller crystals and intracrystalline diffusion. This had profound influence on Sm–Nd geochronology and resulted in isochron ages ranging from 50 to 32 Ma. The youngest age was obtained for a sample, where all garnet crystals are smaller than 2 mm in which light REE profiles are completely or nearly completely homogenized. Thus, only the youngest age represents geologically meaningful event, and 31.7 ± 0.9 Ma age is interpreted as the best estimate of the resetting episode due to high temperature diffusional homogenization of light REE during early Oligocene metamorphism. Older Sm–Nd ages reflect mixed analyses of variably reset individual garnet crystals.Lu–Hf isotopic analyses of bulk garnet fractions, despite yielding high parent/daughter isotopic ratios appeared very scattered and did not allow defining isochron ages. Instead, apparent ages defined by whole rock and individual garnet fractions range from c. 80 to 160 Ma. Very old apparent ages are interpreted as being the consequence of intracrystalline Lu diffusion and preservation of the original Hf distribution, which leads to lower 176Lu/177Hf ratios, and thus steeper (older) isochrons. Back diffusion of Lu during commonly observed resorption played a subordinate role in modifying isotope systematics.